2021
DOI: 10.1038/s41598-021-83822-9
|View full text |Cite
|
Sign up to set email alerts
|

Association of coagulation dysfunction with cardiac injury among hospitalized patients with COVID-19

Abstract: Cardiac injury is a common complication of the coronavirus disease 2019 (COVID-19), and is associated with adverse clinical outcomes. In this study, we aimed to reveal the association of cardiac injury with coagulation dysfunction. We enrolled 181 consecutive patients who were hospitalized with COVID-19, and studied the clinical characteristics and outcome of these patients. Cardiac biomarkers high-sensitivity troponin I (hs-cTnI), myohemoglobin and creatine kinase-myocardial band (CK-MB) were assessed in all … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 44 publications
0
16
0
1
Order By: Relevance
“…26 Another possible mechanism is the direct invasion via angiotensin converting enzyme 2 (ACE2) receptors in cardiovascular system. 3,27 In our study, we not only found that COVID-19 patients with comorbidities were associated with higher mortality, but also the CRP levels are significantly associated with mortality in multivariate Cox analysis, which indicated there would be inflammation response and this was associated with worse outcomes. In addition, IL-6 cytokines were elevated in COVID-19 patients with myocardial injury, justifying the emergence of severity of inflammation, also immune-related markers, like CD3, CD4, CD8 molecules counts and lymphocyte counts were all reduced, more significant in patients with myocardial injury.…”
Section: Discussionmentioning
confidence: 49%
“…26 Another possible mechanism is the direct invasion via angiotensin converting enzyme 2 (ACE2) receptors in cardiovascular system. 3,27 In our study, we not only found that COVID-19 patients with comorbidities were associated with higher mortality, but also the CRP levels are significantly associated with mortality in multivariate Cox analysis, which indicated there would be inflammation response and this was associated with worse outcomes. In addition, IL-6 cytokines were elevated in COVID-19 patients with myocardial injury, justifying the emergence of severity of inflammation, also immune-related markers, like CD3, CD4, CD8 molecules counts and lymphocyte counts were all reduced, more significant in patients with myocardial injury.…”
Section: Discussionmentioning
confidence: 49%
“…These studies examined various aspects of cardiac or myocardial injury among hospitalized patients or patients admitted to the intensive care units. Of all the included studies, 12 (28.5%) were prospective studies [33,35,37,40,42,45,49,55,60,70,72,76]. The 30-day mortality was found to be associated with increased cardiac troponin I (cTnI) (45.1% vs. 23.2%; p=0.005) [33].…”
Section: N Resultsmentioning
confidence: 99%
“…A study in the group of 181 COVID-19-positive patients showed 23.2% of them had cardiac injury diagnosed on the basis of elevated biomarkers (high-sensitivity troponin I, myohemoglobin and creatine kinase myocardial (p < 0.001, >99th percentile)). The median age was 55 (IQR, 46-65) years [7]. A study of 2895 COVID-19-positive patients in New York University School of Medicine showed that cardiac injury was present in 16.8% of patients, and troponin levels (>99th percentile, adjusted for sex and age) were considered to be indicative of myocardial necrosis [8].…”
Section: Frequency and Characteristicmentioning
confidence: 99%
“…Cardiac injury was a crucial and independent risk factor for mortality in COVID-19-infected patients [12,[21][22][23] and mortality was usually higher in the cardiac injury group [7,9,[23][24][25]. Patients with cardiac injury were older [7,11,22,26], had more comorbidities [22,25,26], were mostly male [10,22], had more serious disease [7,22,23] or were more likely to require mechanical ventilation [21,22]. Age is an independent predictor of myocardial injury in COVID-19-positive patients [10].…”
Section: Hospitalisation and Outcomementioning
confidence: 99%